Kreativitas Belajar Siswa Sekolah Dasar Negeri 2 Pemongkong dengan Menggunakan Model Pembelajaran Number Head Together - Hidayati, Baiq Nurul (YASIN, 2021)
This study aims to determine and described the learning creativity of elementary school students using the number head together learning model. This research method is a literature review research method. The stages of this literature review are data collection, data reduction, data display, discussion, and conclusions. The results showed that from 17 articles published from 2010-2020 about the number head together learning model and learning creativity of elementary school students, there were 2 articles that matched these variables. The number head together learning model can increase the learning creativity of elementary school students. The novelty of this research is the connection between one article and another that discusses the same topic. The impact of the results of this study is the increasing number of literature review studies to reinforce existing theories.